(untitled) (Hematology Meeting Reports, 2009)
Myelopoiesis, which involves growth and maturation of granulocytic and monocytic lineages, is highly controlled by lineage-specific hematopoietic transcription factors such as AML1, PU-1, C/EBPa, CBFb, retinoic acid receptor a (RARa) etc. that cooperatively interact with specific DNA sequences and directly activate or repress the expression of myeloid specific genes.